Predicting the tricritical point composition of a series of LaFeSi magnetocaloric alloys via universal scaling. (21st September 2017) - Franco, V; Law, J Y; Conde, A; Brabander, V; Karpenkov, D Y; Radulov, I; Skokov, K; Gutfleisch, O
Abstract: Typically, the most common techniques to determine the order of the phase transition of magnetocaloric materials do not allow a quantitative prediction of the composition that corresponds to the change from first to second order phase transition, i.e. the so-called tricritical point of an alloy series. In this work, we study a series of LaFeSi alloys in which the different Fe/Si ratio produces a change in the order of the transition. We show the quantitative prediction of the tricritical composition analyzing the field dependence of the peak magnetic entropy change. The proposed procedure is also simple to implement, as it does not require any modelling of the experimental data and it only requires temperature and field dependent magnetization experiments. It is shown that the obtained value is in agreement with the results emerging from the most commonly used qualitative techniques.